Progressive Back Pain due to Aspergillus nidulans Vertebral Osteomyelitis in an Immunocompetent Patient: Surgical and Antifungal Management - Mark K. Lyons; Matthew T. Neal; Naresh P. Patel; Holenarasipur R. Vikram (Case Reports in Orthopedics)
Case Report. Aspergillus osteomyelitis is a destructive and progressive infection that has been described both in immunosuppressed and in immunocompetent hosts. We describe a case of lumbar vertebral osteomyelitis in a 61-year-old immunocompetent patient due to Aspergillus nidulans that was successfully treated with a combination of extensive surgical debridement, spinal stabilization, and a prolonged course of antifungal therapy. Imaging demonstrated findings consistent with L3 discitis. The biopsy grew Aspergillus fungus and was treated with vorconizole. Imaging showed progressive destructive osteomyelitis at L3-L4. Patient underwent anterior L3 and L4 partial corpectomies, anterior interbody fusion L3-L5, and posterior T11-S2 pedicle screw and rod fixation. Antifungal treatment resulted in resolution of infection. Aspergillus markers remain negative. One year following definitive treatment, the patient’s back pain remains resolved. Conclusion. Definitive surgical resection of the infection, spinal stabilization, and aggressive antifungal therapy were required to eradicate the infection.